DILAM CONCEPTUAL MODEL: integration of archives, libraries and museums - Simionato, Ana Carolina; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP] (Univ Federal Campina Grande, 2017)
Descriptive principles in archives, libraries and museums present diverse procedures and are consistent with the ways in which their resources are represented, mainly in relation to the description of the image content. In this way, the research problem involves the question of how to promote the integration of the contexts of Archivology, Librarianship and Museology for the digital image resource? The integration proposal between the contexts seeks the convergence of the data of the image treated in the Archivology, Librarianship and Museology, benefiting the recovery and location of the resources by the user. It points out the digital medium and the descriptive principles of the three contexts as factors that subsidize the studies and development of a conceptual model. Thus, the objective of this work is to present the results of this proposal, through the construction of the conceptual model Digital Images for Libraries, Archives and Museums (DILAM) emphasizing their entities and the attributes responsible for the integration to the contexts and the digital image resource. Methodologically it constitutes an applied and exploratory theoretical research. It addresses the entities and attributes of the conceptual model DILAM, in addition to the groups concerning the integration of contexts and the properties of the image content. It is considered that this structure is presented in the integration diagram applicable in the digital environment in which libraries, archives and museums can cooperate by reusing the data and reducing the reworking of the description of digital image resources.
Keywords: Digital image; Representation of information; Metadata